2021
DOI: 10.1002/jsfa.11453
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of duck egg yolk provides novel insights into its characteristics and biofunctions

Abstract: BACKGROUND: Although the importance of phosphorylation in the function of proteins is known, investigation of the protein phosphorylation of duck egg yolk (DEY) is still very limited. This study aimed to conduct a detailed phosphoproteomic study of DEY using immobilized metal affinity chromatography and ultra-high liquid chromatography tandem mass spectrometry.RESULTS: A total of 253 phosphorylation sites assigned to 66 phosphoproteins were identified in DEY, of which VTG-1, VTG-2, and fibrinogen alpha chain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(121 reference statements)
0
0
0
Order By: Relevance
“…It has been reported that dehydroepiandrosterone affected both protein synthesis and phosphorylation level to decrease fat deposition in broiler chickens during embryonic development [13]. Several phosphoproteomics studies have been performed on duck eggs, the phosphoproteins in duck egg white were mainly involved in the binding, transport activity, biological regulation, and metabolic processes [14], and the phosphoproteins in duck egg yolk were mainly involved in binding, catalytic, immune response, and metabolic activity [15]. In our study, phosphoproteomics was employed to dissect the molecular regulation mechanisms of F1 cross chicken cecum infected with S. Enteritidis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dehydroepiandrosterone affected both protein synthesis and phosphorylation level to decrease fat deposition in broiler chickens during embryonic development [13]. Several phosphoproteomics studies have been performed on duck eggs, the phosphoproteins in duck egg white were mainly involved in the binding, transport activity, biological regulation, and metabolic processes [14], and the phosphoproteins in duck egg yolk were mainly involved in binding, catalytic, immune response, and metabolic activity [15]. In our study, phosphoproteomics was employed to dissect the molecular regulation mechanisms of F1 cross chicken cecum infected with S. Enteritidis.…”
Section: Introductionmentioning
confidence: 99%